THE INFLUENCE OF SPAYLATER TRUST AND CONVENIENCE ON CONSUMPTIVE BEHAVIOR OF SHOPEE APP USERS IN BANDUNG - Reskiah Putri Zani; Marheni Eka Saputri (SEAN Institute, 2023)
Shopee launched in 2015, is a leading e-commerce site in Southeast Asia and Taiwan. There are already quite a lot of shopee users using the spaylater payment method, which is around 68%. In light of this, the goal of this study is to determine and analyze the Trust and Convenience of Spaylater on Consumptive Behavior of Shopee Application Users in Bandung partly and concurrently. This study employs a quantitative approach to descriptive research. This study employs a technique of non-probability sampling. There were 384.1 samples collected for this investigation, but the authors added to 385 respondents to reduce the number of respondents' calculation errors. Techniques for data analysis based on descriptive analysis and multiple linear regression analysis. According to the study's findings, trust is in the very good category, convenience is in the reasonably good category, and consumption is in the fairly good area. Based on the findings of multiple linear regression analysis, it can be inferred that there is a positive, one-way link between the variables of trust and convenience and consumptive behavior.